REFORMASI KEMENTERIAN NEGARA (TINJAUAN YURIDIS DAN IMPLEMENTASINYA DALAM PEMERINTAHAN PRESIDEN PRABOWO SUBIANTO) - ADY SUPRYADI; FAHRURROZI FAHRURROZI; AESTHETICA FIORINI MANTIKA; RENA AMINWARA; FITRIANI AMALIA (GANEC SWARA, 2024)
This research aims to examine the reform of state ministries as an effort to improve the organizational structure of the Indonesian government in order to increase the effectiveness and efficiency of government performance in carrying out state functions. In the context of President Prabowo Subianto's government, related to efforts to optimize government management, as well as improving national development policies, it can provide an overview of how the reform of this state ministry will be implemented. Reform of state ministries in Indonesia is generally related to restructuring efforts to improve bureaucratic performance. Since the beginning of the post-New Order reforms, the structure of state ministries has undergone various changes. Among the significant changes that occurred, was a reduction in the number of ministries to create a more efficient and focused government. This state ministry reform process is carried out based on academic studies and evaluations of the effectiveness of existing ministries and state institutions. The main aim is to improve the quality of public services, speed up the decision-making process, and ensure that state ministries can carry out their main tasks and functions optimally.